Questioning Turkish Psychological Counselor Trainees’ Prejudices towards Some Clients: Reflections of the Social Context - Körük, Serdar; Karababa, Alper; Kurt, Ali Ammar (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
The purpose of this study was to reveal the prejudices of psychological counselor trainees towards clients and the sources of these prejudices among a group of Turkish undergraduates in the psychological counseling department. The study group consisted of 39 undergraduates who were continuing their education in the third year. The ages of the students varied between 20 and 23. They were from different parts of Anatolia region in Turkey. The qualitative data obtained from 39 participants underwent content analysis. The themes related to the prejudices were found as crime domain, nationalism domain, LGBT people domain, conservative people domain, and personal domain while the themes related to the sources of prejudices were found as interpersonal domain, personal domain, and media domain. The themes and categories were discussed in relation to the literature on prejudice in psychological counseling and the previous studies that have been conducted.